Ability of sickle cells to scavenge endothelium-derived nitric oxide is reduced. - OLMOS Leopoldo; MOMBOULI Jean-Vivien; WASSERSTRUM Nathan; VANHOUTTE Paul M (Acta Pharmacologica Sinica, 2016)
AIM: To assess the ability of sickle cells to interfere with the release or transfer of endothelium-derived relaxing factor (EDRF) in comparison to normal erythrocytes. METHODS: A perfusion-superfusion bioassay system was used a canine carotid artery with endothelium (donor of EDRF) and a ring of the same vessel without endothelium (detector) were separated by tubing resulting in a five second interval for transfer of EDRF from donor to detector. Changes in isometric tension were monitored in both the donor and the detector preparations. Release of EDRF, as determined by sustained relaxations during the contractions to phenylephrine, was induced by infusing acetylcholine through the donor artery. RESULTS: Superfusion with normal and sickle erythrocytes caused impairment of the endothelium-dependent relaxations in both detector and donor tissues. When infused through the transfer line, sickle cells were less potent than normal erythrocytes in inhibiting relaxation in the detector tissues. In contrast, infusion of either normal erythrocytes or sickle cell through the donor artery caused similar degrees of inhibition in donor and detector arteries. Hemolysates from both types of erythrocytes were equieffective at either site of infusion. CONCLUSION: These results indicate that sickle cells are intrinsically less potent scavengers of EDRF than normal erythrocytes. However, exposure to the endothelium enhances the ability of sickle cells to inhibit lumenal release of endothelium-derived relaxing factor.